Design Tools of Electric Applications Kwh Printing by Short Message Service. Issue 1 (June 2019) - Salahuddin,; Basyir, M.; Tusannalaila, Sharifah
Abstract: The prepaid electric meter is an electrical measuring and recording device used by customers with a prepaid system or so-called prepaid. A system that is able to recharge electric vouchers automatically using SMS and notification to the customer that the balance of electricity will be exhausted. This system is built using SMS gateway method by using GSM sim900 modem. When the power balance is below 10 KWH then the alarm will sound, at the same time the microcontroller will send SMS and miscall to customer's mobile number